Experiment-based Internal Ballistics Simulation of Dual-Thrust Solid Rocket Motors (Global Journals of Research in Engineering, 2023)
A key aspect to a successful simulation of the flow inside the Dual Thrust Solid Rocket Motor DTSRM is the proper definition of boundary and operating conditions as well as fluid properties The experimental pressure-time curve was analyzed and divided into five regimes to be used as inputs for numerical simulations to understand the flow features inside an experimental DTSRM motor and to estimate its thrust The entire motor operation time from ignition to tail-off was examined including two steady-state phases boost and sustain and three transient phases ignition boost-sustain transition and tail-off The grain burnback analysis was carried out to obtain the computational domain for each simulation The operating pressure for each simulation is defined as equal to the measured chamber pressure which was measured at the head end of the motor The results confirmed the capabilities of simulations to explore the flowfield inside the motor and to predict its thrust with remarkable accuracy of less than 5 relative to the experimental measurements in lieu of analytical calculations that are more suited for preliminary calculations and only offer accuracy of about 15 relative to experimental measurements
Keywords: dual-thrust solid rocket motor; internal ballistics; grain burnback; numerical simulation